2007
DOI: 10.1260/026361707785082396
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Basic Dye Adsorption onto Sphagnum Magellanicum Peat

Abstract: ABSTRACT:The purpose of this study was to investigate the adsorption of two Basic dyes, i.e. Basic Blue 3 (BB3) and Basic Orange 2 (BO2), onto Sphagnum Magellanicum peat. The equilibrium studies were carried out at 30 o C and 45 o C, respectively. The equilibrium experimental results were fitted to the Langmuir model to obtain the characteristic parameters. The maximum sorption capacities for each dye were 41 mg/g for BB3 and 92 mg/g for BO2. The magnitude of the a L parameter increased with temperature for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…As a result, development of low cost alternative adsorbents has been a focus of research and a number of low cost adsorbents have been reported in the literature. These include clays [10,11], red mud [12], fly ash [13], steel wastes [14], peat [15], and diverse biomasses derived from plants, animals and microbes [16 -22]. These biosorbents are generally by-products or waste from large scale industrial operations and agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, development of low cost alternative adsorbents has been a focus of research and a number of low cost adsorbents have been reported in the literature. These include clays [10,11], red mud [12], fly ash [13], steel wastes [14], peat [15], and diverse biomasses derived from plants, animals and microbes [16 -22]. These biosorbents are generally by-products or waste from large scale industrial operations and agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of basic dyes on high cellulosic concentration is also governed by coulombic interaction and ion exchange (Contreras et al, 2007) as it becomes partially negatively charged when immersed with water and interact with cationic species in water.…”
Section: Comparative Study Of Present Adsorbents With Previous Studiesmentioning
confidence: 99%
“…In view of that, a pseudo-kinetic model may be appropriate to approximate the process dynamics of protein adsorption [65,66].…”
Section: Adsorption Isothermsmentioning
confidence: 99%